Optimalisasi peran media sosial dalam meningkatkan efektivitas green marketing pada sektor industri dan bisnis - Sepridayana, Sepridayana (Nur Science Institute, 2026)
One of the increasingly prominent marketing approaches is green marketing, which emphasizes sustainability and environmental responsibility. This study aims to analyze the role of social media in enhancing the effectiveness of green marketing and to identify key factors influencing its success, including consumer engagement, digital interaction, the role of influencers, and information transparency. This research employs a qualitative approach using a literature review method by examining various academic journals, books, and relevant sources. The results indicate that social media plays a strategic role in delivering sustainability messages in a broad, interactive, and persuasive manner, thereby increasing environmental awareness, strengthening positive brand image, and enhancing consumer loyalty toward green products. Furthermore, the integration of educational content, creative digital campaigns, and influencer collaboration significantly improves the credibility and attractiveness of green marketing strategies. However, the implementation of social media-based green marketing still faces several challenges, such as low environmental literacy, regulatory limitations, and the risk of greenwashing practices. Therefore, transparent, educational, and sustainable digital communication strategies are essential to optimize the effectiveness of green marketing and to generate positive impacts on environmental sustainability and long-term business performance.